Late Post-Operative Complete Heart Block after Ventricular Septal Defect Repair Procedure - Imtiaz, Sana; Akhtar, Khurram; Mehmood, Amjad; Akbar, Hajira; Sadiq, Nadeem; Ara, Andaleeb (Pakistan Armed Forces Medical Journal, 2022)
In congenital cardiac surgery, intracardiac repair procedures like ventricular septal defect (VSD), atrioventricular septal defect and tetralogy of fallot (TOF) are associated with conduction system injury. Fewer cases are reported describing life threatening complication of late post-operative complete heart block. We are reporting 2 patients who presented with late complete heart block after ventricular septal defect repair and managed by permanent pacemaker placement in AFIC Cath lab.